Redefined Measure of Early Neurological Improvement Shows Treatment Benefit of Alteplase Over Placebo. Issue 4 (April 2020) - Agarwal, Shashank; Scher, Erica; Lord, Aaron; Frontera, Jennifer; Ishida, Koto; Torres, Jose; Rostanski, Sara; Mistry, Eva; Mac Grory, Brian; Cutting, Shawna; Burton, Tina; Silver, Brian; et al.
Abstract : Background and Purpose—: The first of the 2 NINDS (National Institute of Neurological Disorders and Stroke) Study trials did not show a significant increase in early neurological improvement, defined as National Institutes of Health Stroke Scale (NIHSS) improvement by ≥4, with alteplase treatment. We hypothesized that early neurological improvement defined as a percentage change in NIHSS (percent change NIHSS) at 24 hours is superior to other definitions in predicting 3-month functional outcomes and using this definition there would be treatment benefit of alteplase over placebo at 24 hours. Methods—: We analyzed the NINDS rt-PA Stroke Study (Parts 1 and 2) trial data. Percent change NIHSS was defined as ([admission NIHSS score−24-hour NIHSS score]×100/admission NIHSS score] and delta NIHSS as (admission NIHSS score−24-hour NIHSS score). We compared early neurological improvement using these definitions between alteplase versus placebo patients. We also used receiver operating characteristic curve to determine the predictive association of early neurological improvement with excellent 3-month functional outcomes (Barthel Index score of 95–100 and modified Rankin Scale score of 0–1), good 3-month functional outcome (modified Rankin Scale score of 0–2), and 3-month infarct volume. Results—: There was a significantly greater improvement in the 24-hour median percent change NIHSS among patients treated with alteplase compared with the placebo group (28% versus 15%; P =0.045) but not median delta NIHSS (3 versus 2; P =0.471). Receiver operating characteristic curve comparison showed that percent change NIHSS (ROCpercent ) was better than delta NIHSS (ROCdelta ) and admission NIHSS (ROCadmission ) with regards to excellent 3-month Barthel Index (ROCpercent, 0.83; ROCdelta, 0.76; ROCadmission, 0.75), excellent 3-month modified Rankin Scale (ROCpercent, 0.83; ROCdelta, 0.74; ROCadmission, 0.78), and good 3-month modified Rankin Scale (ROCpercent, 0.83; ROCdelta, 0.76; ROCadmission, 0.78). Conclusions—: In the NINDS rt-PA trial, alteplase was associated with a significant percent change improvement in NIHSS at 24 hours. Percent change in NIHSS may be a better surrogate marker of thrombolytic activity and 3-month outcomes.